On the non-specificity of slurs - Frigerio, Aldo; Tenchini, Maria Paola (Rivista Italiana di Filosofia del Linguaggio, 2020)
A quite neglected question pertaining to the classification of the different theories on slurs concerns their extendibility to other pejoratives and expressives in general. In this paper, we show that the linguistic behaviour of pejoratives is similar to that of slurs. Therefore, a theory on slurs that is also extendible to other pejoratives and expressives is, other things being equal, preferable to a theory that is not applicable to other classes beyond slurs. Slurs seem to differ from other pejoratives as the latter seem to target single persons and not a class of persons. This implies that the derogatory component of slurs does not seem to project outside negative, conditional, modal and interrogative contexts. Nevertheless, we demonstrate that this difference is deceptive due to some specific features of the other pejoratives, such as targeting negative characteristics or having a fuzzy extension